2018
DOI: 10.1051/medsci/201834f109
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic combined with hysteroscopic repair or operative hysteroscopy in the treatment of symptomatic cesarean-induced diverticulum

Abstract: Objective: The postmenstrual bleeding with cesarean-induced diverticulum is a bothersome symptom and can be confused with other abnormal-uterine bleeding disease. The aim of the present study was to evaluate the efficacy and safety of laparoscopic combined with hysteroscopic repair vs operative hysteroscopy in treatment of symptomatic cesarean-induced diverticulum. Methods: Eighty-two women with cesarean-induced diverticulum who underwent either laparoscopic combined with hysteroscopic repair or operative hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The treatment of symptomatic USD includes drug therapy and surgery. Drug therapy is limited, and surgery can better manage the defect, but there are still different ideas about the choice of surgery (13)(14)(15)(16)(17)(18). Surgical treatment usually includes hysteroscopic resection and vaginal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of symptomatic USD includes drug therapy and surgery. Drug therapy is limited, and surgery can better manage the defect, but there are still different ideas about the choice of surgery (13)(14)(15)(16)(17)(18). Surgical treatment usually includes hysteroscopic resection and vaginal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Reported outcomes, either by patients or clinicians, are summarised in Table 3. The most frequently reported gynaecological outcomes were prolonged menstrual bleeding [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], postmenstrual spotting [5,8,9,25,35,[44][45][46][47][48][49][50], dysmenorrhoea [5,8,9,25,27], dyspareunia [5,27,46] and (chronic) pelvic pain or abdominal pain [5,24,25,27,34,40,46,51,52...…”
Section: Systematic Review Of Literaturementioning
confidence: 99%
“…Prevalence of abnormal adhesive placenta [26,27], successful vaginal birth after CS [27,[53][54][55] and uterine rupture or dehiscence [27,[56][57][58][59][60][61][62][63] were reported as obstetric outcomes. Fertility-related niche therapy studies reported on wish to conceive (secondary subfertility) [26,27,33,52], pregnancy [25,26,33,39,40,42,64] and miscarriage rate [26,27,33,39,42,43], the risk of caesarean scar pregnancy [27,33,40] and live birth rate [26,27,40,43]. Subsequent pregnancies were followed after niche therapy in four studies: mode and timing of delivery [39,42], risk of abnormal adhesive placenta [40] and risk of uterine dehiscence or rupture [39,40,43] were reported.…”
Section: Systematic Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] The previous study found that laparoscopic combined with hysteroscopic repair had better efficiency in improving the abnormal uterine bleeding, regulating the normal menstruation duration, and increasing the pregnancy rate. [ 6 ] Other research demonstrated that hysteroscopy was more effective in the treatment of cesarean section scar diverticulum, while resectoscopic treatment was highly effective in women with abnormal uterine bleeding. [ 7 ] Therefore, different surgical treatment methods have their own advantages and disadvantages, which should be selected according to the type of disease.…”
Section: Introductionmentioning
confidence: 99%